Single-Dose Versus Multiple-Dose GnRH Agonist for Luteal-Phase Support in Women Undergoing IVF/ICSI Cycles: A Network Meta-Analysis of Randomized Controlled Trials - Liu, Yang; Wu, Yanzhi; Pan, Zhengmei; Jiang, Fangjie; Lu, Youhui; Meng, Yushi (Frontiers in Endocrinology, 2022)
Background: Although gonadotropin-releasing hormone (GnRH) agonist has been introduced as a beneficial luteal phase support (LPS), the optimal strategy of GnRH agonist remains unclear. This network meta-analysis was therefore performed to determine the comparative efficacy and safety of multiple-dose versus single-dose GnRH agonist protocol for LPS in patients undergoing IVF/ICSI cycles. Methods: We searched relevant studies in PubMed, Embase and the Cochrane Registry of Controlled Trials (CENTRAL) from their inception util to September 2021. Live birth, clinical pregnancy rate, multiple pregnancy rate, and clinical abortion rate was evaluated. Pairwise and network meta-analysis were conducted using RevMan and ADDIS based on random-effects model, respectively. Moreover, the prioritization of protocols based on ranking probabilities for different outcomes were performed. Results: Sixteen RCTs met our eligibility criteria. Pairwise meta-analysis showed that multiple-dose protocol of GnRH agonist was effective for increasing live birth rate (OR 1.80, 95% CI 1.15 to 2.83, p=0.01) and clinical pregnancy rate (OR 1.89, 95% CI 1.01 to 3.56, p=0.05) as well as decreasing clinical abortion rate (OR 0.55, 95% CI 0.34 to 0.90, p=0.02). Meanwhile, single-dose protocol of GnRH agonist was effective for increasing clinical pregnancy rate (OR 1.45, 95% CI 1.11 to 1.89, p=0.007) and multiple pregnancy rate (OR 2.55, 95% CI 1.12 to 5.78, p=0.03). However, network meta-analysis only confirmed that multiple-dose protocol of GnRH agonist was the best efficacious strategy for live birth rate (OR 2.04, 95% CrI 1.19 to 3.93) and clinical pregnancy rate (OR 2.10, 95% CrI 1.26 to 3.54). Conclusions: Based on the results of NMA, multiple-dose protocol may be the optimal strategy for patients undergoing IVF/ICSI cycles owing to its advantage in increasing live birth and clinical pregnancy rate. Moreover, single-dose protocol may be the optimal strategy for improving multiple pregnancy rate. However, with the limitations, more RCTs are required to confirm our findings.